A STUDY ON THE MARKET PERFORMANCE OF DAIRY PRODUCTS OF DIFFERENT BRANDS IN HYDERABAD - P. RADHIKA, SK. MAHAMOOD, K. KAREEMULLA and (The Journal of Research, PJTSAU, 2019)
India ranks first in milk production, accounting for 18.5% of world production with a total production of 155.5 Mt during 2015-16 and with a percapita availability of 337 g/day (NDDB, 2017). About 46% of the total milk produced is consumed in liquid form while another 47% is converted into traditional products like cottage butter, ghee, paneer, khova, curd, malai etc. The remaining seven per cent of the milk goes into the production of western style products like milk powders, processed butter and processed cheese (Singh, 2008).